Ответы и объяснения

2014-02-08T21:00:31+04:00
A1.  a) y' = ( 2 +  e^{x})'= e^{x}
б) y' = (9 e^{x}+5x)'=9 e^{x}+5
в) y'=(3x+ e^{x})'=3+ e^{x}
г) y'=(10 e^{-x})'=10 e^{-x}*(-1)=-10 e^{-x}
A2) a) y'=( 2^{x}+cosx)' =  2^{x}*ln2-sinx
б) y'=(x* e^{-x})'=x'* e^{-x}+x*( e^{-x})'= e^{-x}-x* e^{-x}= \frac{1}{ e^{x} }- \frac{x}{ e^{x} }= \frac{1-x}{ e^{x} }
в) y' = ( 4^{x}-7* e^{-x})' =  4^{x}*ln4-7* e^{-x}*(-1)= 4^{x}*ln4 + 7* e^{-x}
A3) f (x) = 2* e^{-x}-1
урав. касательной: y = f (x₀) + f '(x₀) (x-x₀)
f (x₀) = f (0) =  2* e^{0}-1=2*1-1=1
f '(x) =  2*e^{-x}*(-1) = -2* e^{-x}
f '(x₀) = f '(0) = -2e° = -2
y = 1 - 2(x-0) = 1-2x
B1. y' = ( 2^{-x}*sinx)' = ( 2^{-x})'*sinx +  2^{-x}*(sinx)' =  2^{-x}*ln2*(-1)*sinx +       2^{-x}*cosx = - 2^{-x}*ln2*sinx +  2^{-x}*cosx
B2.  \int\limits^2_0 { 2e^{x-1} } \, dx = 2* e^{x-1}= 2*e^{2-1}-2* e^{0-1}= 2e- \frac{2}{e}=  \frac{2 (e^{2}-1) }{e}
C1. y'=( \frac{ e^{x} }{x})'= \frac{( e^{x})'*x- e^{x}*x'  }{ x^{2} }  = \frac{ e^{x}*x- e^{x}  }{ x^{2} } = \frac{ e^{x}(x-1) }{ x^{2} }
крит. точки:
 \frac{ e^{x}(x-1) }{ x^{2} } =0
x-1 = 0
x² ≠0

x = 1
x ≠ 0
------- (0) ---- [1] ++++++
функция убывает на (-беск.;0)U(0;1] ; возрастает на [1; +беск.)
Xmin  = 1
Ymin =  \frac{ e^{1} }{1}=e